Single female tenants in South Delhi - gender, class and morality in a globalizing city - Bernroider, Lucie (Gender, place and culture, 2018)
Based on ethnographic data gathered over 12 months of fieldwork with unmarried women living alone or in flat-shares in different middle class South Delhi localities, this article traces the way shifting gendered norms – often epitomized by growing numbers of single women households – are negotiated within class specific and highly localized contexts of the residential neighborhood. Despite growing economic opportunities for middle class and elite women, cultural anxieties surrounding the notion of ‘delayed’ marriage and women living outside of the familial or marital home persist and obstruct attempts at establishing independent households. Single women experience difficulties finding apartments to rent; have to contend with hostile intrusions from neighbors; or feel obliged to self-monitor their behavior within their neighborhoods. As South Delhi’s liberalised urban landscape has become home to an increasingly globalized, consumerist middle class, disciplinary measures such as curfews, regulations over houseguests and increased surveillance simultaneously indicate a middle class recalibrating its gendered social coordinates by proving its commitment to values of female propriety. While popular discourses draw juxtaposed imaginaries of the ‘modern’ and the ‘traditional’ in their depictions of increasing individualism and a loosening of ‘traditional’ role expectations, this article demonstrates the need to consider the different structural conditions and local inflections in which struggles over women’s agency take place. Looking beyond the supposedly universalizing forces of globalized consumer modernity, the residential neighborhood hereby provides a view into the lived experiences of – at times incongruous – mechanisms at play in societies undergoing social change.
Gesehen am 08.08.2019